Abrolhos Magmatic Province petrogenesis and its link with the Vitória-Trindade Ridge, Southeast Brazilian Margin, South Atlantic Ocean. (December 2022) - Mothé Maia, Thais; Costa dos Santos, Anderson; Castro Valente, Sérgio; Reis Viana Rocha-Júnior, Eduardo; Pacheco Watson de Barros, Guilherme; Heilbron, Mônica; de Morisson Valeriano, Claudio; Arena, Michele
Abstract: The Abrolhos Magmatic Province (AMP) is an example of an igneous province with about 63, 000 km 2 located at the Continent-Ocean Boundary (COB), into the Southeast Brazilian Margin. The AMP emerges as five small islands (Santa Bárbara, Redonda, Siriba, Sueste, and Guarita) which integrate the Abrolhos Archipelago located about 55 km offshore Brazil. The studied rocks belong to a transitional basalt series of alkaline affinity, with evolved rocks with high TiO2 contents. This work presents new detailed fieldwork mapping, petrographic, and whole-rock chemistry data, besides Sr–Nd isotopic compositions from AMP rocks. Mapped magmatic rocks in the Abrolhos Islands have been described as extrusive rocks, but we point out that they are shallow intrusions, mostly sills, and should be grouped into diabase units based on fieldwork and textural features. The AMP lithogeochemical and isotopic data suggest the operation of differentiation processes more complex than simple fractional crystallization or AFC. Our model mixing calculations based on new and compiled Sr-Nd-Pb isotopic data suggest a mixture with a prevailing depleted asthenosphere mantle source (represented by DMM; ca. 80%) metasomatized by an enriched mantle I (EMI) component (≤ 10%) and a possible HIMU-type constituent (up to 10%) in the AMP genesis. The assimilation of subducted slabs of the oceanic crust associated with the HIMU signatures is possibly linked to the Brasiliano Event due to the range of the AMP Nd TDM model ages, from 407 to 767 Ma. A viable mechanism for the EMI end-member contribution could either be a physical detachment of the South American subcontinental lithospheric mantle during the breakup of the Gondwana or lithospheric delamination of the South American plate caused by an edge-driven convection mechanism. The AMP and the Vitória-Trindade Ridge (VTR) show an eastward decreasing age pattern from the older ca. 60 Ma Abrolhos Province to the younger Martin Vaz and Trindade Islands ( ca. 4 – 0.1 Ma), located ca. 1200 km away from the Brazilian coastline. The volcanic alignment between the VTR and AMP, along with the overlap of geochemical and isotopic data of their different igneous rocks, cannot be a random feature but instead represent the sampling of similar shallow mantle reservoirs, thus suggesting a cogenetic relationship. Finally, a possible petrogenetic link between the AMP and VTR magmatism is discussed. Highlights: We detail new field mapping, petrographic and whole-rock chemistry from AMP. New Sr–Nd isotopic ratios suggest a DMM source enriched by EMI and HIMU components. Mapped magmatic rocks in the Abrolhos Islands are shallow intrusions, mostly sills. Operation of differentiation processes more complex than simple FC or AFC. We discuss a possible petrogenetic link between the AMP and VTR magmatism.